In situ preparation of ultrafine Ru nanocatalyst supported on nitrogen‐doped layered double hydroxide by nitrogen glow discharge plasma for catalytic hydrogenation of N‐ethylcarbazole. (20th May 2020) - Shi, Jiaming; Bai, Xuefeng
Abstract : Ultrafine Ru nanoparticles (RuNPs) supported on nitrogen‐doped layered double hydroxide (Ru/LDH) were in situ prepared by nitrogen glow discharge plasma (nGDP) without adding any chemical reducing agents or stabilizers. The as‐synthesized Ru/LDH catalysts were characterized by X‐ray diffraction, X‐ray photoelectron spectroscopy, transmission electron microscopy, and Fourier transform infrared spectroscopy. During treatment with nGDP, the reduction of Ru 3+ and nitrogen doping were carried out simultaneously. The resulting RuNPs has a narrow particle size distribution of 1.41–2.61 nm, an ultrafine average particle size of 1.86 nm, and were uniformly dispersed on nitrogen‐doped LDH. The complexation of RuNPs and O/N‐containing functional groups on LDH improve the catalytic activity and stability of Ru/LDH. The catalyst exhibited excellent properties for the hydrogenation reaction of N ‐ethylcarbazole (NEC). The conversion of NEC and the selectivity of 12H‐NEC were 100% and 99.06% for 1 hr at 120°C and 6 MPa H2, respectively. The mass hydrogen storage capacity was 5.78 wt%. The apparent activation energy was 35.78 kJ/mol. Abstract : Ultrafine Ru nanoparticles supported on nitrogen‐doped layered double hydroxide (Ru/LDH) were in situ prepared by nitrogen glow discharge plasma (nGDP) without adding any chemical reducing agents or stabilizers. During treatment with nGDP, the reduction of Ru 3+ and nitrogen doping were carried out simultaneously. The as‐prepared Ru/LDH exhibited favorable catalytic and repetitive performance in the N ‐ethylcarbazole hydrogenation reaction.